Upaya Peningkatan Sikap Peduli Lingkungan Melalui Kegiatan Ekstrakurikuler Robotik di MTSN 3 Pekanbaru - Anita Febriani; Al Hidayati; Haris Tri Saputra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
MTSN 3 Pekanbaru is a school that has a mission of "Character, Excellence and Environmental Insight". One of its missions is to develop students' interest in talent through superior robotics, research, academic and tahfiz class programs. And another vision is to develop awareness and love for the environment through environmental care activities. Based on this mission and vision, an effort is needed to provide knowledge about environmental care attitudes to students in an interesting way, one of which is robotic extracurricular activities by making smart trash can robots (Smart Trash Bin). Based on the existing problems, the solutions provided consist of 1) Socialization regarding environmental care attitudes. 2) training on waste management. 3) Workshop on making intelligent trash can robots (Smart Trash Bin). The method of implementing the activities are 1) the preparation stage, 2) the implementation stage, 3) the evaluation and reporting stage. The results obtained are that students are able to explain the difference between waste and how to manage it and are also able to make smart trash cans.